Studi Literatur: Pencemaran TPA Air Sebakul dan Pemanfaatan Sampah Organik Rumah Tangga dengan Biogas - Eva Satriani; Radeni Ilyan Putra; Meistian Herizon; Reflis Reflis; Satria P Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The Air Sebakul Landfill (TPA Air Sebakul) in Bengkulu City is facing significant environmental pressure due to increasing waste volume and suboptimal management methods. This study aims to analyze the types of environmental pollution caused by activities at the landfill and to explore household waste management based on biogas technology. Literature review shows that the open dumping system leads to water, air, and soil pollution. Leachate from waste contaminates groundwater sources, while greenhouse gas emissions worsen air quality and impact public health. Moreover, soil quality declines due to the accumulation of hazardous substances. On the other hand, organic household waste, which makes up the majority of the city’s waste composition, has high potential to be utilized as a raw material for biogas production. Biogas technology at household scale can offer a sustainable waste management solution, reducing landfill pressure while generating energy and organic fertilizer. The successful implementation of this management system requires synergy among government, community, and related institutions in the form of policies, education, and technical support to realize an environmentally friendly and sustainable waste management system in Bengkulu City.